Enhancing Cultural Resonance: A Decision Support System for Selecting Islamic Names using the Analytical Hierarchy Process - Ahmad, Fauzan; Hanafiah, Adelia (International Journal of Enterprise Modelling, 2024)
The selection of Islamic names represents a deeply rooted cultural tradition intertwined with spiritual significance, historical resonance, and familial heritage within the Muslim community. This research endeavors to develop a Decision Support System (DSS) utilizing the Analytical Hierarchy Process (AHP) methodology to navigate the multifaceted process of choosing Islamic names. The study integrates quantitative analysis with cultural sensitivity to create a structured framework for evaluating names based on criteria encompassing meanings, cultural relevance, pronunciation, and familial connections. Expert opinions and user perspectives are incorporated to establish criteria weights, providing a systematic approach to prioritize attributes aligned with cultural traditions and personal preferences. The implementation of the DSS aims to empower individuals and families to make informed, culturally resonant choices while fostering transparency, reducing subjective biases, and enhancing understanding of the profound significance inherent in Islamic names. Furthermore, the research acknowledges the adaptive nature of the DSS, capable of accommodating evolving cultural norms and diverse perspectives within the Muslim community. Ultimately, this study seeks to bridge the gap between tradition and modern decision-making methodologies, fostering a deeper appreciation for the rich heritage encapsulated within the selection of Islamic names.